Innate immunity and Toll-like receptor signaling in the pathogenesis of scleroderma: advances and opportunities for therapy. Issue 6 (November 2018) - Brown, Max; O'Reilly, Steven
Abstract : Purpose of review: Systemic sclerosis (SSc) is an autoimmune connective tissue disease in which inflammation and cytokine dysregulation leads to skin fibrosis. Toll-like receptors (TLRs) are conserved pattern recognition receptors, recognizing pathogens danger-associated molecular patterns (DAMPs) that elicit a cascade of proinflammatory signaling. Recently, TLRs have been found to be critically important in SSc pathogenesis, with increased levels of the TLRs and their ligands present in the disease. Animal models have also been pivotal in delineating the role of these innate immune receptors in SSc. This current review examines the role of TLRs and the most recent evidence of the role of DAMPs and how these may be exploited therapeutically. Recent findings: Increasingly, studies have demonstrated the key roles of TLR4 and other intracellular TLRs in mediating fibrosis in SSc patients and animal models. TLR4 activation appears a key point and novel DAMPs, expressed upon tissue damage, appear critical in mediating the profibrotic effect through a downstream enhancement of transforming growth factor β. Deletion of Tenascin-C or a splice variant of fibronectin ameliorates animal models of skin fibrosis. Intracellular, nucleic acid sensing, TLR8 is critical in activating macrophages to secrete profibrotic molecules. The mechanism involves histone modification through epigenetic modifying enzymes. Summary: TLRs are key therapeutic targets in SSc.